Comprehensive Evaluation of Fiscal Efficiency and Digitalization: Implications of Presidential Instruction No. 1/2025 on Teacher Welfare Professionalism (Universitas Pamulang, 2025)
This research examines the impact of Presidential Instruction No. 1/2025 on the efficiency of education budget allocations, particularly on the Teacher Professional Education (PPG) and teacher certification programs in Indonesia. Using a systematic literature review method and a qualitative approach, this study collected data from reliable sources, including the official website of the Ministry of Education, Culture and Research, the Central Bureau of Statistics, and media publications. The results show that budget efficiency policies led to a revision of the PPG participant quota target, which was originally set to exceed 800,000 teachers in 2024 to around 400,000 teachers in 2025. However, there was a significant increase in participation in digital training that supports the modernization of learning processes, as well as additional funding allocations for learning innovations that improve the quality of training. On the other hand, the decline in the number of teacher certifications, especially in remote areas, reveals serious challenges in equitable distribution of education quality and competency verification. This study concludes that the implementation of budget efficiency policies must be balanced with intensive mentoring strategies, continuous evaluation and improved inter-agency coordination to ensure an inclusive and highly competitive education transformation. The findings of this study provide a comprehensive picture of the dynamics of policy change and its implications for teacher professionalism and welfare, and provide room for improvement in the future. This research opens up opportunities for the development of targeted policy strategies to support the transformation of Indonesia's education system in the future.